(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate the cytoprotective role of the Cyanacobalamin on the detrimental effects of heat –induced stress on splenic tissue. Study Design: An Experimental study Place and Duration of the Study: Department of Anatomy, Basic Medical Sciences Institute, Jinnah Postgraduate Medical Centre, Karachi from January 2010 to April 2010. Materials and Methods: Forty five Albino rats (180-200 grams) were selected and divided into group A (Control), group B (Heat - induced) and group C (Protective). Each group was further subdivided into three subgroups, based on the period of the study. The animals of the subgroups B and C received heat and the temperature was set at 42 C for six hours daily. Group C (C1, C2 and C3) animals were protected with Cyanocobalamin (BETOLVEX) at the dosage of 0.8 mg/ kg of body weight intraperitonealy, two hours before heat induction. Then animals were sacrificed according to their time duration, spleens were removed and fixed in alcoholic formalin for 24 hours .Then tissue were processed in ascending strengths of alcohol from 70 to 100%,cleared in xylene, infiltrated and embedded in paraffin.5 micron thick sections were stained with haemotoxylin and eosin and e. Blood samples were collected in EDTA K3 containing vacutainers for the hormonal assay of plasma ACTH level. Results: in group B animal’s heat-stress alters the immunoarchitecture of the spleen; size of all comportments of the white pulp reduces with the appearance of the tingitble body macsophages and individual apoptotic cells and free apoptotic bodies. This group also shows significant increase in plasma ACTH levels. Whereas the splenic architecture and plasma ACTH level in group C animals return to normal by the cytoprotective effects of the Cyanocobalamin. Conclusion: The current study demonstrates the beneficial effects of the Cyanocobalamin to alleviate the detrimental effects of the heat-stress on the immune organs.